2006
DOI: 10.1007/s10620-005-9040-x
|View full text |Cite
|
Sign up to set email alerts
|

Chondrosarcomatous Differentiation in Diffuse-Type Gastric Carcinoma

Abstract: The vast majority of malignant neoplasm of the stomach is represented by epithelial tumors composed of tubular, acinar, or papillary structures or consisting of a complex mixture of isolated cells with variable morphologies in combination with glandular, trabecular, or solid nests. The most commonly used classification systems are the WHO and the Lauren systems. The diffuse type of gastric cancer is more aggressive, is located in the proximal part of the stomach, is more frequent in young patients, and frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Upon review of the literature, 76 cases were identified (Table II) [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. The clinical features of patients with gastric carcinosarcoma appeared to be nonspecific with epigastric pain, weight loss, and melena, as the most common complaints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Upon review of the literature, 76 cases were identified (Table II) [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. The clinical features of patients with gastric carcinosarcoma appeared to be nonspecific with epigastric pain, weight loss, and melena, as the most common complaints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Par ailleurs, certaines tumeurs primitives peuvent donner de métastases gastriques, comme le mélanome, le cancer du sein et le cancer de poumon, un cas de chondrosarcome métastatique dans l'estomac ayant été observé [3]. L'apparition d'un carcinome gastrique avec différentiation chondrosarcomateuse a été rapportée une seule fois dans la littérature [1]. Mais notre observation est la première d'une tumeur constituée uniquement de tissu chondrosarcomateux au niveau gastrique.…”
Section: Discussionunclassified
“…La plupart des cancers de l'estomac sont de tumeurs épithéliales composées de structures tubulaires, acinaires ou papillaires. Néanmoins des composants sarcomateux ont été décrits rarement et même un cas de carcinome gastrique épithélial de type diffus avec différenciation chondrosarcomateuse en son sein a été observé [1]. Nous rapportons un cas de chondrosarcome primitif pur de l'estomac sans composante épithéliale.…”
Section: Primary Chondrosarcoma Of Stomachunclassified